ANALYZING BANKRUPTCY CANCELLATION THROUGH THE PRINCIPLE OF JUSTICE: A CASE STUDY OF INTIDANA COOPERATIVE - Adiel Mischa Kristianto; Suteki Suteki; Mahoro Jean Claude Geofrey (Faculty of Law, Universitas Lampung, 2025)
Indonesian bankruptcy law, regulated under Act Number 37 of 2004, has yet to fully realize its principles, resulting in legal uncertainty and gaps in implementation. A notable example is the Intidana Cooperative bankruptcy case, where a cassation ruling was later overturned through a Review Court decision. This study analyzes the revocation of Intidana Cooperative’s bankruptcy through the lens of the Principle of Justice in Act Number 37 of 2004, reinforced by John Rawls’ Theory of Justice. Using descriptive analysis of legal documents, government policies, and prior studies, the research finds that the Judicial Review decision upheld the Principle of Justice by recognizing cooperative members as the least advantaged party. Petitioners for bankruptcy were themselves cooperative members, while other members lacked the power to influence cooperative actions without a resolution from the Cooperative Members’ Meeting, placing them in a vulnerable position requiring judicial protection. The study concludes that while justice was realized in this case, existing provisions safeguarding the interests of cooperative members in bankruptcy require further review to ensure equitable outcomes for all parties.